Peningkatan Pengetahuan mengenai Kurang Energi Kronik (KEK) dan Gizi pada Ibu Hamil di Masa Pandemi Covid-19 - Rifatul Masrikhiyah; Anggray Duvita Wahyani; Yuniarti Dewi Rahmawati; Rifqi Fery Balfas; Hanari Fajarini (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the nutritional problems that occur in pregnant women is chronic energy deficiency (KEK) in pregnant women. KEK is a condition caused by an imbalance between intake and energy and protein requirements. Data for Basic Health Research (Riskesdas) in 2018 shows the prevalence of the risk of KEK in pregnant women (15-49 years) in Indonesia is still quite high at 17.3%. One of the causes of KEK is knowledge about low nutritional food intake. The purpose of this PkM is to increase the level of knowledge of pregnant women about nutrition and KEK. The method used in this PkM is counseling through lecture media. The results of the PkM show an increase in knowledge of pregnant women before (pre-test) and after (post-test) counseling on nutrition and KEK